2018
DOI: 10.1007/s10704-018-0279-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of an image-based numerical model for predicting the microstructure–property relationship in alumina trihydrate (ATH) filled poly(methyl methacrylate) (PMMA)

Abstract: Particulate composites are found in a wide range of applications. Their heterogeneous microstructure affects their bulk behavior and structural performance, however tools for predicting this important structure-property relationship are still lacking. In this study, a numerical method that can provide predictions of the mechanical response of a particulate polymeric matrix composite as a function of volume fraction and particle mean diameter is presented. The work is derived for an alumina trihydrate filled po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 61 publications
(74 reference statements)
4
10
0
1
Order By: Relevance
“…However, when compared to glass, PMMA has high flammability, low resistance to abrasion and to scratch. Due to these limitations, different types of fillers [1][2][3][4][5][6][7][8][9][10][11][12][13] have been used in an attempt to improve the properties of PMMA, forming PMMA matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, when compared to glass, PMMA has high flammability, low resistance to abrasion and to scratch. Due to these limitations, different types of fillers [1][2][3][4][5][6][7][8][9][10][11][12][13] have been used in an attempt to improve the properties of PMMA, forming PMMA matrix composites.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the PBX material properties depend on the binder system, volume fraction and crystal size distribution [1,[9][10][11][12][13]. The polymer binder system is often challenging to characterise owing to its highly nonlinear, time-dependent behaviour [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies observed that interfacial debonding always initiated around the larger particles in the high explosive PBX 9501 as the larger particles act as stress concentration sites [9,12,20,21]. In addition, Fleming et al [22] and Kimura and Oyumi [23] showed that the particle size also affected the high explosive performance; for the same volume fraction, particles with a larger size distribution were more sensitive to shock ignition compared to those with smaller particle size.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang [11] desarrolla modelos numéricos capaces de predecir las propiedades mecánicas de materiales compuestos reforzados con partículas, con aplicaciones específicas en materiales compuestos de PMMA/ATH. Los resultados teóricos fueron comparados con resultados experimentales obtenidos por Zhang en un estudio previo [12].…”
Section: Introductionunclassified